Mengatasi Masalah dengan Transformasi Teknologi di Sektor Pertanian untuk Mewujudkan Ketahanan Pangan Nasional yang Berkelanjutan - Wahyu Dwi Ramadhani (Journal of Economics Development Issues, 2023)
Indonesia was once a self-sufficient country in rice during the New Order era with the Green Revolution program. However, in 2021 the harvested area for rice plants is in the range of 10.41 million hectares, which if examined more deeply, this figure has decreased in the previous year, namely 2020, which according to the figure range is 245.47 thousand hectares or has decreased by around 2.30 %. Then in 2021, rice production will also experience a decrease of around 31.36 million tons or if it is presented the decrease will be in the range of 0.45 percent. The decline in agricultural land and crop production is not only a problem in this study. Another problem arises, namely the lack of use of technology and the decreasing number of millennial farmers. To overcome these problems researchers used qualitative research methods and used secondary data to be analyzed again. Technological transformation is the main key to this problem so that national food security is strong and sustainable